A Perspective Review on Laser Assisted Microjoining - Bag, Swarup (Recent Patents on Mechanical Engineering, 2011)
In the era of miniature, laser microjoining has been evolving as a prospective smaller scale manufacturing process. The latest development in the field of laser technology brought new opportunities for laser to join wide variety of materials used in microsystems. In the growing technological field like micro-electro-mechanical systems (MEMS) and biomedical applications, the laser microjoining has the potential for application as encapsulation of miniature. However, the feasibility of microjoining depends on pulse modulation strategy and wavelength for selective range of laser power and laser irradiation intensity. Development and adaptation of new methodology also brings the flexibility in micro scale joining process with reduced defects and sound quality. A number of patents on the design of apparatus and methodology in this area show the signature of the development of the field. The current review article is focused on various aspects of micro scale joining process in the perspective of practical application. First, experimental investigation on the type of laser, process conditions, materials and feasibility of microjoining processes is reviewed. Secondly, on-line monitoring and control of the microjoining process is analyzed. An extensive part of the article is devoted to the review of numerical process model. It is anticipated that at ultrashot pulsed laser, the non-Fourier heat conduction analysis is more appropriate to signify rapid propagation of heat wave. Except from current prospective application, the future research direction and potential applications are also discussed. In a nutshell, the review article provides an overview of microjoining process which is extracted from literature and is required for promising development in microsystem technology.
Keywords: welding process